Advances in power and energy engineering : proceedings of the 8th Asia-Pacific Power and Energy Engineering Conference (APPEEC 2016), Suzhou, China, 15-17April 2016 /: proceedings of the 8th Asia-Pacific Power and Energy Engineering Conference (APPEEC 2016), Suzhou, China, 15-17April 2016. ([2016]) - Unknown
No abstract available